Mormonism in dialogue with contemporary Christian theologies - Paulsen, David L.; Paulsen, David L. (Mercer Univ. Press, 2007)
Misunderstanding, misrepresentation, and ensuing acrimony have too often characterized Mormon relations with other Christians. In pursuing "discussions that lead to understanding," this volume brings together, for the first time, a broad range of scholars from Mormon and other Christian traditions. Replacing polemics and apologetics with dialogue, these exchanges show how the full spectrum of contemporary theologies can be informed by uniquely Mormon ideas, and correlatively, how Mormon thought can be illuminated through the study of key ideas of the foremost theologians of the twentieth and twenty-first centuries, including Karl Barth, Reinhold Niebuhr, Paul Tillich, Langdon Gilkey, Robert McAfee Brown, Clark Pinnock, Rosemary Radford Reuther, Linda Thomas, Dwight Hopkins, David Griffin, and David Tracy. Besides providing succinct but illuminating presentations of basic Christian theological topics, this work discloses Mormon perspectives, virtually unknown in academia, on these topics. In content, as well as methodology, this book provides promising contexts for mainline Christian-Mormon conversations in particular and an exemplary model for intra-faith dialogue in general.